2017
DOI: 10.1177/1071100716685526
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Magnetic Resonance Imaging and Stress Radiographs in the Evaluation of Chronic Lateral Ankle Instability

Abstract: Level III, retrospective cohort, comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
0
30
0
1
Order By: Relevance
“…1 ). Twenty-four studies underwent full-text screen, and 9 studies were excluded for the following reasons: inconsistent reference standards among subjects [ 21 , 27 29 ], studies on other lesions associated with chronic ankle instability [ 30 33 ], and heterogeneous population with inadequate data for chronic injury group [ 34 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). Twenty-four studies underwent full-text screen, and 9 studies were excluded for the following reasons: inconsistent reference standards among subjects [ 21 , 27 29 ], studies on other lesions associated with chronic ankle instability [ 30 33 ], and heterogeneous population with inadequate data for chronic injury group [ 34 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Imaging diagnosis is usually non-invasive and can be of value when physical tests are ambiguous [ 16 ]. Results for the four including imaging diagnostic techniques have been reported; however, the diagnostic accuracy of each imaging technique is variable in different studies, partly due to different reference standards applied [ 20 , 21 ]. Our study set arthroscopic or surgical findings as the gold standard to investigate four imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, in order to further con rm the ligament injury and decide whether there is need to repair the lateral ligament, the stress position of the patients in this study was examined by intraoperative uoroscopy after anesthesia or intraoperative xation of the fracture. And for the reason that the anterior drawer test and talus tilt test differed greatly for individual, the stress image of ankle joint on the healthy side compared with that of the lesion side should be as the judgement standard [12]. If one of the following conditions occurred, it should be judged that the lateral instability of the ankle joint existed and the lateral ligament required repairing: Inclination of talus more than 10 degrees or anterior displacement of talus more than 8 mm under stress radio-graphs; Compared to the opposite side, inclination of talus more than 5 degrees or anterior displacement of talus more than 5 mm.…”
Section: The Diagnosis Of Acute Degree Injury Of Lateral Ankle Ligamementioning
confidence: 99%
“…More recently, Kim et al 19 found stronger sensitivity (76%-84%) and specificity (83%-92%) in identifying ATF injuries using MRI. Finally, Jolman et al 22 found that MRI assessment of patients with CAI had strong sensitivity (83%) but weak specificity (53%). Thus, for CF injuries, MRI is likely to be useful for identifying true negatives while providing poor true positive identifi-cation.…”
Section: Instrumented Assessment and Imaging Of Lateral Ankle Ligamentsmentioning
confidence: 99%